Novel roles for CG7379/ING1 in tumour progression: a study of migration and invasion using in vivo and in vitro epithelial systems - Rusu, Alexandra Doina (2020)
The ability of cancer cells to invade and metastasize is the hallmark of cancer that sets apart malignant from benign tumours. Approximately 90% of cancer-related deaths can be attributed to cancer’s ability to spread. A recent in vivo genetic screen that focused on the identification of tumour progression modulators identified CG7379, the fly orthologue of human ING1, as a potential invasion suppressor. ING1 is a type II tumour suppressor gene with well-established roles in transcriptional regulation of genes that control cell proliferation, response to DNA damage, oncogene-induced senescence and apoptosis. Recent work suggests a possible role for ING1 in cancer cell invasion and metastasis; however the underlying molecular mechanism has not been studied thus far.